2016
DOI: 10.1038/cdd.2016.142
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenesis contributes to intestinal cell differentiation

Abstract: The intestinal epithelium undergoes a continual process of proliferation, differentiation and apoptosis. Previously, we have shown that the PI3K/Akt/mTOR pathway has a critical role in intestinal homeostasis. However, the downstream targets mediating the effects of mTOR in intestinal cells are not known. Here, we show that the ketone body β-hydroxybutyrate (βHB), an endogenous inhibitor of histone deacetylases (HDACs) induces intestinal cell differentiation as noted by the increased expression of differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 52 publications
9
93
0
Order By: Relevance
“…Although it would be impossible to prove that all phenotypic characteristics of a human enterocyte require SLFN12, these results certainly suggest that some may. These SLFN12 effects may seem modest, but they are consistent in magnitude with changes in mucosal atrophy that others have observed in vivo [37, 38] and the effects of differentiating stimuli on Caco-2 cells in vitro [3943]. Since many markers of enterocytic differentiation are enzymes or transport proteins, small changes in such proteins can catalyze greater downstream effects.…”
Section: Discussionsupporting
confidence: 78%
“…Although it would be impossible to prove that all phenotypic characteristics of a human enterocyte require SLFN12, these results certainly suggest that some may. These SLFN12 effects may seem modest, but they are consistent in magnitude with changes in mucosal atrophy that others have observed in vivo [37, 38] and the effects of differentiating stimuli on Caco-2 cells in vitro [3943]. Since many markers of enterocytic differentiation are enzymes or transport proteins, small changes in such proteins can catalyze greater downstream effects.…”
Section: Discussionsupporting
confidence: 78%
“…Recent study have showed that proliferative cells at the base of the intestinal crypt are characterized by a glycolytic metabolic phenotype, whereas differentiated cells have an oxidative phosphorylation phenotype, which is in line with the findings showed by sun et.al and Wang et.al, implying that nutritional states are closely associated with alteration of intestinal barrier function. Interesting, our previous study has revealed monocarboxylate transporter 4 (MCT4) expression is significantly increased in intestinal mucosal tissue of IBD patients, which is correlated with intestinal mucosal inflammation, and MCT4 is involved in establishment and maintenance of epithelial polarity and lactate transporters .…”
Section: Introductionsupporting
confidence: 87%
“…Wang et.al, 22 implying that nutritional states are closely associated with alteration of intestinal barrier function. Interesting, our previous study has revealed monocarboxylate transporter 4 (MCT4) expression is significantly increased in intestinal mucosal tissue of IBD patients, which is correlated with intestinal mucosal inflammation, 23 and MCT4 is involved in establishment and maintenance of epithelial polarity and lactate transporters.…”
Section: Andmentioning
confidence: 99%
“…In the developing brain, ketone bodies generated from leucine may also act as a substrate for the oxidative generation of energy. Furthermore, ketone bodies are known to play a regulatory roles in the differentiation of intestinal epithelial cells . A study showed that a ketogenic diet induced the expression of HMGCS2 during the differentiation and proliferation of intestinal epithelium, suggesting that HMGCS2 was regulated by ketone bodies .…”
Section: Discussionmentioning
confidence: 99%